2013
DOI: 10.1016/j.ydbio.2013.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Direct activation of a mouse Hoxd11 axial expression enhancer by Gdf11/Smad signalling

Abstract: A Hoxd11/lacZ reporter, expressed with a Hoxd11-like axial expression pattern in transgenic mouse embryos, is stimulated in tailbud fragments when cultured in presence of Gdf11, a TGF-β growth/differentiation factor. The same construct is also stimulated by Gdf11 when transiently transfected into cultures of HepG2 cells. Stimulation of the reporter in HepG2 cells is enhanced where it contains only the 332 bp Hoxd11 enhancer region VIII upstream or downstream of a luciferase or lacZ reporter. This enhancer cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…This is seen from both gain-and loss-offunction studies (Liu, 2006, McPherron et al, 1999. For at least one gene, Hoxd11, Gdf11 operates by smad2/3 signalling to a cis enhancer sequence (Gaunt et al, 2013). As expected, Gdf11 is expressed in the region of the primitive streak at the time that new Hox patterns are being generated (McPherron et al, 1999).…”
Section: Temporal Collinearity Without Timed Chromatin Openingmentioning
confidence: 59%
“…This is seen from both gain-and loss-offunction studies (Liu, 2006, McPherron et al, 1999. For at least one gene, Hoxd11, Gdf11 operates by smad2/3 signalling to a cis enhancer sequence (Gaunt et al, 2013). As expected, Gdf11 is expressed in the region of the primitive streak at the time that new Hox patterns are being generated (McPherron et al, 1999).…”
Section: Temporal Collinearity Without Timed Chromatin Openingmentioning
confidence: 59%
“…Therefore, beyond a pre-existing chromatin architecture, the precise timing of distinct signals during the progression of embryogenesis appears to determine a global collinear activation of Hox gene transcription: Wnt3 and Wnt3a signaling induces anterior genes , and Cdx proteins stimulate trunk/central genes (Neijts et al 2017), whereas Gdf11 further activates group 11 Hox genes (Gaunt et al 2013) as well as groups 12 and 13 (our unpublished data). While the temporal progression within these various groups of genes responding to the same factor remains to be understood, it may rely on a progressive and directional opening of a chromatin structure (see below).…”
Section: Directionality Of the Hox Clockmentioning
confidence: 87%
“…However, we did not detect any canonical SBEs within 20 kb of the DOCK4 transcriptional start site (data not shown). Since prior studies had shown that a large proportion of Smad-binding sites are found outside of promoter-proximal regions at putative enhancer elements (Kennedy et al 2011;Morikawa et al 2011;Schlenner et al 2012;Gaunt et al 2013), we considered whether Smad proteins occupy distal SBEs at the DOCK4 locus. To this end, we analyzed available Smad3 ChIP-seq (chromatin immunoprecipitation [ChIP] combined with deep sequencing) data (GSE51509) obtained from TGF-b-stimulated A549 cells (Isogaya et al 2014) and found two significant Smad3 peaks in the first intron of DOCK4 at +45 kb and +125 kb (Fig.…”
Section: Tgf-b Potently Induces Expression Of Dock4 Via the Smad Pathwaymentioning
confidence: 99%